Subsidized overexpansion of Chinese firms - Han, Miao; Zhang, Dayong; Bi, Xiaogang; Huang, Wei (Elsevier, 2019)
This paper examines the economic consequences of public subsidies to listed firms in China. It reveals that public subsidies can significantly increase the chance of firm overinvestment. However, they do not necessarily resolve the underinvestment problem. These results appear robust when we test various types of subsidies separately, as well as when we analyze the influence of subsidies on the investment-Q sensitivity. Further investigation shows that dividend payout has an important moderating role in this relationship between subsidies and investment. Firms with subsidies, especially those that pay higher cash dividends, have lower future stock returns and valuations than comparable non-subsidized firms. Overall, the main findings of this paper signal a clear government failure to correct market failure in the Chinese capital market. © 2019